ANALYSIS OF HUMAN RESOURCE DEVELOPMENT OF ENGLISH LANGUAGE CENTER IN MANADO - Yayuk Christianti, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The research’s goal is 1) exploring the human resource development strategies at the English Language Center in Manado, and 2) identifying the factors which might encounter the strategies. The research type is descriptive that describe about an overview and explanation of the human resource development strategies at the English Language Center in Manado.The findings figure out that 1) the human resource development strategy at the English Language Center in Manado is throughout formal education, where employees have got opportunity to pursue higher education profoundly. An employee training is the following strategy; however, it is not conducted regularly in asmuch as limited budget, which restricts the training time as well. Due to the lack of budget and stipulated training time that is impactful to an unoptimal of human resource development strategies at the English Language Center in Manado. The hindrance factors of human resource development strategies at the English Language Center belong to external obstacles such as rapid economic changes, changes in legislation, and political developments. Internal obstacles is a part of the strategic planning which is ineffective,organizational structure which is not central and not well organized and limited budget. However, limited budget takes a significant impact as a barrier to human resource development strategies at the English Language Center in Manado among those mentioned